Orthoamides and Iminium Salts LXXXII: Cleavage of Orthoamides of Alkynecarboxylic Acids by Elemental Iodine – A New Method for the Preparation of Vinylogous Guanidinium Salts - Kantlehner, Willi; Stieglitz, Rüdiger; Kreß, Ralf; Frey, Wolfgang; Tiritiris, Ioannis (Synthesis, 2012)
Orthoamides of six alkynecarboxylic acids, possessing reactive substituents in 3-position, are transformed by elemental iodine to the corresponding vinylogous guanidinium iodides. The constitution of two of the iodides was established by crystal-structure analysis.
Keywords: orthoamides; alkynecarboxylic acids; cleavage reactions; iodine; vinylogous guanidinium iodides